Sexual risk behaviors among the taxi drivers in Davao City - Amoguis, Ariel Innsence R. (Animo Repository, 2002)
This study assesses the STD/HIV/AIDS risk behavior among the taxi drivers in Davao City. Specifically, the study obtained information about the men's (a) background characteristics, (b) marriage, (c) sexual experiences, (d) level of awareness, access to and use of condoms, (e) level of awareness and experiences regarding STD, (f) level of awareness, information source, and knowledge about transmission routes and protection against the disease as well as views about HIV/AIDS, and (g) exposure to HIV/AIDS information and intervention programs.The survey utilized the individual face-to-face interview with two age categories of men - 18-24 and 35-45 years old. Simple random sampling was done to select eighty drivers as sampUple sim(/Uze). An in-depth interview was done to three drivers who had low, moderate and high sexual risk behavior.The mean age of the respondents was 35.01 years. Majority were married and live with families and relatives. They had an average of 11.06 years of formal schooling. Majority were Catholics. The mean monthly income was P6,506.25. More than half, took alcohol four weeks prior to the survey and less than half ever tried drugs particularly marijuana.All the drivers were sexually experienced. The average age for coital debut was 17.95 years. Majority had their girlfriends and no money was involved during their first sexual experience. In the past 12 months, seventy drivers had vaginal sex with their spouse or girlfriend. Only one-tenths of the men had multiple sexual partnership. All the respondents had heard of condoms. Less than half had used condoms. The most common reason for non-use was condoms were not sexually gratifying. Majority claimed to use condoms with unpaid partners.Majority had heard of STD. They can give one correct symptom. None of the men had STD in the past 12 months.All the men had heard of HIV and AIDS. More than half perceived that the two are the same. The men had moderate to high knowledge of HIV transmission and about the means of protection from the disease. Despite these, erroneous notions and beliefs against an infected mother, student and worker were noticed. Half believed that they had no chance of acquiring HIV/AIDS.Generally, the study found that a great majority of the taxi drivers were not at risk of acquiring and transmitting STD/HIV/AIDS. The men who practiced safer sex behavior were much greater in number than those with unsafe sex behavior.